(untitled) (Indian Journal of Animal Production and Management, 2025)
Background: Tendons are strong connective structures that link muscles to bones, facilitating mobility and stability within the musculoskeletal system. Tendon injuries exhibit a characteristically slow and often incomplete healing process. Objectives: the objective of this research was to an evaluate and a compare efficacy of Boswellia serrata extract and bovine follicular fluid on the clinical and histological healing of Achilles tendon defects in a canine model. Methods: Twenty-seven adult local dogs were used in this study. A core lesion defect was surgically induced in Achilles tendon of all animals. The dogs were divided randomly to three equal groups (n=9): A Control Group, where the defect was treated with Autologous PRF alone; Treated Group 1 (B.S. Group), treated with 1.5 mL of B. serrata extract and Autologous PRF; and Treated Group 2 (FF Group), treated with 1.5 mL of bovine follicular fluid and Autologous PRF. The healing process was monitored for 60 days and assessed via macroscopic clinical evaluation (lameness, swelling, redness), and histopathological examination (at days 14, 30, and 60) post-surgery. Results: Clinically, the B.S. group showed the most rapid improvement, with a significant reduction in lameness by (day 9) post-surgery compared to the FF and the control groups. Histopathologically, both treatment groups showed an absence of inflammation at day 14, unlike the control group. At day 60, the FF group demonstrated superior tissue regeneration, characterized by the complete restoration of the tendon’s structural normality with highly organized regular collagen fibers. Conclusion: Both Boswellia serrata extract and bovine follicular fluid accelerate the healing of Achilles tendon defects when combined with PRF. Boswellia serrata provides faster clinical recovery and stimulates early collagen synthesis, while bovine follicular fluid promotes superior long term structural and histological restoration of the tendon tissue.